Radical prostatectomy vs radiotherapy in high-risk prostate cancer patients: two centre experience - Ulys, Albertas; Ulyte, Agne; Dziameshka, Pavel; Sukonko, Oleg; Krasny, Sergei; Polyakov, Sergei; Smailyte, Giedre (Lietuvos chirurgija, 2015)
Background/objectiveThere are no randomized trials on the comparative effectiveness of radical prostatectomy (RP) and radiotherapy (RT) for high-risk prostate cancer. Our aim was to compare treatment outcomes of high-risk prostate cancer after RP and RT, including overall survival (OS), biochemical-progression-free survival (bPFS) and disease-progression-free survival (dPFS), using two cancer treatments centers’ patient data.MethodsData on high-risk prostate cancer patients between 2005 and 2009 were retrospectively reviewed in two cancer centers: National Cancer Institute, Vilnius, Lithuania and N.N. Alexandrov National Cancer Centre of Belarus, Minsk, Belarus; 210 patients were included in the study group treated with RP (n = 174) or RT (n = 36). The mean follow-up time was 5.6 and 6.6 years, respectively.ResultsLower T stage was an independent predictor of better OS (p = 0.01) and bPFS (p = 0.03). Only the highest Gleason score ≥8 was significantly predictive of a worse OS (p = 0.05), bPFS (p = 0.02) and dPFS (p = 0.001). A high PSA level was predictive of a worse bPFS (p = 0.007 for PSA ≥20) and dPFS (p = 0.008 for ≥20). The treatment modality in this study was insignificant after T stage, Gleason score and PSA level adjustment for OS, bPFS survival and dPFS survival (p = 0.17, p = 0.39, p = 0.20).ConclusionsThe T stage, Gleason score and pretreatment PSA level are significant factors for OS, bPFS survival, and dPFS survival of highrisk prostate cancer patients. Treatment option (RP or RT) was not an independent predictor of survival in this study.
Keywords: high-risk prostate cancer; radical prostatectomy; radiotherapy